An Analysis of Pronunciation in Word Stress Towards Students of Sixth Semester of English Education at UIN Raden Intan Lampung - Adam, Nuflihin Surya; Hidayat, Agus; Kholid, Muhammad Ridho (Journal of Linguistics and Social Sciences, 2023)
Stress placement in English words is conduct with complicated rules. Hence, assigning stress correctly in English words is still a challenge for learners. This research explored the production of English word stress by 23 students of the sixth semester at Islam State University Raden Intan Bandar Lampung. This research used a qualitative approach, and the data were recorded by giving a task to pronounce 15 words. PRAAT software was utilized to analyze the recordings, including measuring the pitch, intensity, and duration as indicators. The result illustrated that the students word stress pronunciation was avarage. Almost all the students were able to distinguish the placement of stress correctly, with a percentage of 82% on two syllables, 51% on three syllables, and 67% on four syllables. Mother tongue influence, local accent and lack of exposure in utilized word stress also contribute the problem